Peripheral retinal irradiation with low-energy red light can effectively and safely delay the progression of myopia - Yong Zhang; Wei Chen; Wenwen Xu; Zhiwei Li; Guoying Mu; Yixuan Zhang (BMJ Open Ophthalmology)
Aims To determine whether peripheral retinal irradiation with low-energy red light can effectively and safely delay the progression of myopia.Methods The guinea pigs (age, 2 weeks) were used. The central or peripheral retina was exposed to red light for 3 min each at 9:00 AM and 5:00 PM daily. At day 28, examinations were performed to assess the condition of axial length, the cornea and lens, and the central choroid thickness. The ratio of axial length at a given time to the baseline axial length was used to assess the axial length growth.Results Under the same energy density mode, illuminance (energy density) on the retina layer of peripheral irradiation is less than that of central irradiation. Under myopia induction, after 4 weeks of red light irradiation, the axial length ratios of the central and peripheral irradiation groups were 1.09±0.02 and 1.07±0.02, respectively, both significantly lower than the axial length ratio of 1.11±0.01 in the group with only myopia induction. Peripheral irradiation outperformed central irradiation in delaying axial elongation (p<0.05). Under the premise of myopia induction, peripheral irradiation but not central irradiation at 0.6 mW/cm² still delayed axial elongation. Both central and peripheral irradiation increased central choroidal thickness, with peripheral irradiation having a more pronounced effect.Conclusion Peripheral retinal irradiation with low-energy red light can effectively and safely slow axial growth while increasing central choroidal thickness. The follow-up period for the current study is 28 days, and the long-term safety of red light therapy for myopia necessitates further investigation.